Innovating transparent glass ceramics based on Ga2S3 - GeS2 - CsCl - Ledemi, Y. [UNESP]; Bureau, B.; Calvez, L.; Roze, M.; Guillevic, E.; Audebrand, N.; Poulain, M.; Messaddeq, Y. [UNESP]; Zhang, X. H. (My University, 2009)
In this paper, we describe the preparation of glass ceramics in the Ga2S3 - GeS2 - CsCl system. Visible and infrared transmitting glass ceramics were reproducibly obtained by appropriated heat treatment of the base glass. Crystals with controllable size of about 40 nm were homogeneously generated in the glassy matrix. X-ray diffraction characterizations have shown that gallium acts as nucleating agent in this material, giving rise to α-Ga2S3 crystals. Improved thermomechanical properties such as dilatation coefficient and resistance to fracture propagation have been observed in the prepared glass ceramics.
Keywords: Chalco halides; Crystallization; Glass-ceramics; Infrared glasses